Does Mild to Moderate Renal Dysfunction in Non-Dialysis Dependent Patients (Journal of Surgical Sciences, 2020)
Objectives: Algorithms of risk stratification for coronary artery bypass grafting (CABG) do not include a weighting for preoperative mild to moderate renal impairment defined as a serum creatinine 130 to 199mmol/L, which may impact mortality and morbidity after CABG. Hence our first objective was to ascertain the effect of a mild-to-moderate elevation in the preoperative serum creatinine level on post-operative outcomes. Our second objective was to ascertain which patient variables contributed to an increase in the serum creatinine level in association with coronary artery bypass grafting.Materials and methods: We reviewed the prospectively collected data from the cardiac surgical database, which holds clinical information on all the patients undergoing cardiac surgery at our department since July 2014 to June 2017. A total of 101 patients who had known pre-existing mild to moderate renal disease and who were undergoing first-time coronary artery bypass grafting with cardiopulmonary bypass were recruited for the study. Patients were divided, based on preoperative serum creatinine level, into 3 groups as follows: Group A: creatinine level of less than 130μmol/L; Group B: creatinine level of 130 to 159μmol/L; and Group C: creatinine level of 160μmol/L or greater.Result: Multivariate logistic regression showed that elevation of the preoperative serum creatinine level to 130μmol/L or greater increased the likelihood of hemodialysis postoperatively (P